Characteristics of the bilateral isometric force - time and rate of force development - time curve of leg extensors in high trained serbian male fencers and general trained population - Milic, M.; Ivanovic, J.; Dopsaj, M. (Brazilian Journal of Biomotricity, 2013)
The main aim of the study was to define characteristics of the Force - time (F - t) and Rate of Force Development - time (RFD - t) curve of bilateral voluntary isometric muscle force of leg extensors of Serbian international male epee fencers. The second aim of the study was to define differences between fencers (N=12), as a specific trained group of athletes and group of students of Faculty of sport and physical education from University of Belgrade (N=13) as a control group of healthy and generally trained population. In order to assess the characteristics of the F - t isometric leg extensor force, high sensitive tensiometric probes and the standardized leg press test were used. The measurement range was defined by 12 variables for the contractile characteristics of the leg extensor isometric muscle force - 1) the level of achieved maximal force - FmaxLEGEXTISO, 2) the time necessary to reach maximal force - tFmaxLEGEXTISO 3) the indicator of the basic (general) level of rate of force development - RFDFmaxLEGEXTISO, 4) the Basic Index of Synergy - IndexSNGbasic, 5) the indicator of the specific level of rate of force development - RFD50%LEGEXTISO, three indicators for evaluating the special level of the explosive force development, i.e. leg extensor explosiveness, 5) measured at 250ms - RFD250msLEGEXTISO, 6) measured at 180ms - RFD180msLEGEXTISO, 7) measured at 100ms - RFD100msLEGEXTISO, 8) the indicator of achieved maximal level of Rate of Force Development - RFDmax, 9) the time necessary to reach maximal level of Rate of Force Development - tRFDmax, 10) the level of Force at maximal level of Rate of Force Development - FRFDmax, and 11) the indicator of relation between RFDFmax and RFDmax. The results of multivariate statistical method (MANOVA) showed that there is only one statistical significant difference between observed variables, RFDFmaxLEGEXTISO, F=4.413, p=0.047. According to the presented results it is possible to conclude the following: 1) variables F - t and RFD - t curve of leg extensors are not enough discriminative to show differences between fencers and general trained population; 2) Serbian fencers didn`t have adequate general and specific training to establish better contractile leg extensors abilities; 3) variables F - t and RFD - t curve of leg extensors are not essential in the competitive efficiency in the fencing sport. In the future study shall observe different competitive level of fencer`s population, characteristics at female fencing athletes, different age groups, and also establish relation among F - t and RFD - t variables with competition performance of fencers.